Academic Fraud Dalam Perkuliahan Daring Ditinjau Dari Teori Fraud Gone Dan Konformitas Kelompok Sebagai Pemoderasi - Siti Nursa'adah; Efendri (LP. Ma'arif Janggan Magetan, 2022)
This study aimed to examine the effect of the GONE fraud theory with conformity of group as a moderating variable on academic fraud in students on the online learning system during the pandemic of covid-19. The content of the analysis showed student’s perceptions at a University in Jakarta regarding internal and external factors that encouraged academic fraud. The total of samples in this study were 300 students. The data is a primary data obtained from questionnaires. The results showed that greed, opportunity, and exposure had a positive and significant effect on academic fraud for students, while need had no relation with academic fraud for students. The analysis of the moderating variable was able to show that group conformity was categorized as a moderating predictor.